Equity research lindt & sprüngli: what is the flavor of the future - Sousa, Mariana Inês Gonçalves Teixeira de (2022)
This Equity Research intends to analyze Lindt & Sprungli’s stock and the potential gains of purchasing the stock until the end of 2022. It explores several industry trends and their impact on the company’s value in the foreseeable future. Afterwards, a DCF valuation is performed, having in consideration expectations on the company’s growth, and a multiples valuation is undertaken, giving a perspective on the value of the company based on industry values. Subsequently, a risk analysis is performed alerting the investors for the potential negative incidents and their effect on the value of the company. At the end, an estimated share price value of 128478.41 CHF for the end of 2022 was obtained, leading to a BUY recommendation.